Integrin CD11c regulates B cell homeostasis - Hou, Lifei; Sin, Yi-Cheng; Chen, Yue; Yuki, Koichi (Frontiers in Immunology, 2024)
CD11c is widely known as a cell surface marker for dendritic cells, but we recently showed that it regulates neutrophil and T cell functions. Because we found that CD11c knockout (KO) mice had lower blood B cell counts, we characterized B cell profile in developmental stages. We found that CD11c KO recirculating and mature B cells was significantly fewer compared with wild type, associated with exaggerated proliferation and apoptosis. Because they did not express CD11c, we sought for the possibility of CD11c-mediated non-intrinsic regulation of B cell proliferation and apoptosis. Here we hypothesized that dendritic cells, major cells expressing CD11c would regulate B cells indirectly. The proteomics of dendritic cells cultured in vitro indicated the downregulation of macrophage migration inhibitory factor (MIF). Less MIF was also confirmed by ELISA. Furthermore, plasma MIF level was significantly lower in naïve CD11c KO mice. Because MIF regulates B cell survival, we demonstrated a novel regulatory mechanism of naïve B cells via CD11c.